Serpiginous choroidopathy - Kristine Corpus, MD; Andrew Bijasa, RT; Egidio Jose Fortuna, MD; Narciso Atienza Jr., MD (Philippine Journal of Ophthalmology)
Objective: To describe a case of serpiginous choroidopathy.